Corrosion of low carbon steel in buffered and non-buffered acidic geofluid (geothermal fluid) - Brondial, Yolanda P. (Animo Repository, 2005)
In this study, the effectiveness of the β-chloropionic acid sodium-β-chloropropionate (BCPA-NaBCP) buffer was tested to evaluate the rate of corrosion of low carbon steel in a buffered and in a non-buffered acidic geofluid, five factors were used (pH of buffer, concentration buffer, time of immersion, temperature and velocity of buffered solution) whereas for the non-buffered acidic geofluid three factors were taken (time of immersion, temperature and velocity of buffered solution) The geofluid and the low carbon steels were obtained from the Tiwi Geothermal Plant of Philippine Geothermal, Inc. Experiments were done using the Armfield corrosion kit with two test coupons placed in each beaker in a single time to minimize ‘odd’ results from untypical metal samples. Corrosion rates were measured by direct weighing after a known period of immersion. Data was analyzed through graphs and model adequacy testing, then, confidence interval estimation procedures were carried out. Laboratory experiments showed that the rate of corrosion in a buffered acidic geofluid is 63% lower than that in a non-buffered acidic geofluid. From the analyses of the graphs and interactions of the different factors involved, interesting results were observed. First, a model equation was verified using another set of data and it was found out that the predicted values and the actual experimental values are significantly close to one another. Second, for a difference in temperature of 60Co, the rate of corrosion in a buffered solution is very small, almost negligible as compared to the non-buffered solution. This further strengthened the effectiveness of the BCPA-NaBCP buffer system in the corrosion of low carbon steel.